DYNAMIC RESPONSE OF MULTI-ROBOT COORDINATED TOWING SYSTEM TO WAVES - ZHAO XiangTang; ZHAO ZhiGang; SU Cheng; WEI QiZhe; ZHENG XiaoYan (Jixie qiangdu)
This paper introduces a multi-robot coordinated parallel system for sea towing. Due to the force and direction of the floating-base are constantly changing, it is easy to overturn the crane. Firstly, the system is divided into two parts: floating robot and suspended system, and the dynamic model of the two are analyzed by using hydrodynamic theory and ball-pendulum model. Then according to the characteristics of fluid-solid coupling, the concrete steps of solving the system response to waves are analyzed. Finally, the displacement of floating-base, swing of suspended object and tension of rope are obtained by comparing and simulating the system under wave condition. The conclusion is a good basis for the optimization and control of the system.